FORMULATION AND PHYSICAL PROPERTIES TEST OF NANO CREAM PREPARATION PURIFIED EXTRACT OF KENIKIR LEAF (ETDK) AND TAMPOI FRUIT PEEL EXTRACT (EKBT) - Ika Ristia Rahman; Sulastri Herdaningsih (Jurnal Ilmiah Farmako Bahari, 2021)
This research has been conducted under the title “formulation and physical properties test of nano cream preparations purified extract of Kenikir leaf (ETDK) and Tampoi fruit peel extract (EKBT)”. This study has formulated a nano cream with a purified extract of Kenikir leaf (ETDK), Tampoi fruit peel extract (EKBT), and a combination of ETDK and EKBT. This study aims to determine the purified extract of Kenikir leaves. The purified extract of Tampoi fruit peel can be formulated as nano cream preparations and to determine the physical parameters (organoleptic test, homogeneity, pH, type of nano cream, spreadability, adhesion, and particle size) for the result of the nano cream. The results of the organoleptic test were described and the physical properties of the nano cream were analyzed by using Excel application. Organoleptic testing of the combination of ETDK and EKBT nano cream formula gave a reddish-white color with an aqueous consistency. The ETDK nano cream formula gave a white bone colour with a watery consistency. In contrast, the nano cream formula with EKBT gave a brownish white colour with a watery consistency. It gives a distinctive smell of extract. The third test of nano cream formulas showed that the physical properties of this nano cream preparation met the standard requirements for physical tests. Test the physical properties that meet the pH requirements, type of nano cream, spreadability, adhesion, and particle size, and all three formulas produced an average particle of less than 300nm.